Evaluating internal and external knowledge sources in firm innovation and productivity: an industry perspective - Audretsch, David Bruce; Belitski, Maksim (R & D management, 2023)
Both internal knowledge – investment in internal R&D and information and communication technologies (ICT) as well as external knowledge – knowledge spillovers and active collaboration with partners are rapidly fostering firm productivity and innovation. In this study, we investigate the role of internal and external knowledge in firm productivity and innovation. In addition, we test interactions between investment in R&D and ICT as well as between knowledge spillovers and knowledge collaboration in their association to firm innovation and productivity. We use a recombinant innovation approach and four samples for firms in manufacturing, creative, ICT and science, and professional services industries during 2002–2014 and for pre‐and post‐crisis periods to perform our analysis. In addition to innovation and productivity, we also examine the role of internal and external knowledge as a conduit to the development of innovation internally and the co‐creation of innovation with external partners. Our results lead to managerial and policy implications.